2023
DOI: 10.1002/mds.29306
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic Nucleus 4 Degeneration and Cognitive Impairment in Isolated Rapid Eye Movement Sleep Behavior Disorder

Abstract: Background: Cholinergic nucleus 4 (Ch4) degeneration is associated with cognitive impairment in Parkinson's disease and dementia with Lewy bodies, but it is unknown if Ch4 degeneration is also present in isolated rapid eye movement sleep behavior disorder (iRBD). Objective: The aim was to determine if there is evidence of Ch4 degeneration in patients with iRBD and if it is associated with cognitive impairment. Methods: We analyzed the clinical and neuropsychological data of 35 iRBD patients and 35 age-and sex-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Although cholinergic activity in NREM sleep is reduced, cholinergic signaling increases during and regulates REM sleep ( 38 ). Studies have also demonstrated reduced volumes of cholinergic basal forebrain nuclei in PD patients with cognitive impairment ( 39 41 ), possibly leading to an upregulation of cholinergic receptors in response to cholinergic neuron loss ( 42 44 ). Additionally, the role of GABAergic neurons in the basal forebrain deserves mention, as they play a significant role in influencing theta oscillations ( 45 ) and spindle activity ( 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although cholinergic activity in NREM sleep is reduced, cholinergic signaling increases during and regulates REM sleep ( 38 ). Studies have also demonstrated reduced volumes of cholinergic basal forebrain nuclei in PD patients with cognitive impairment ( 39 41 ), possibly leading to an upregulation of cholinergic receptors in response to cholinergic neuron loss ( 42 44 ). Additionally, the role of GABAergic neurons in the basal forebrain deserves mention, as they play a significant role in influencing theta oscillations ( 45 ) and spindle activity ( 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing cortical cholinergic dysfunction specifically characterised a group of iRBD patients with cognitive decline in another study with a small sample [70]. Grey matter density of the basal nucleus of Meynert, the main origin of cortical cholinergic innervation, was significantly reduced in 35 iRBD patients and reduction was associated with poorer performance in a working memory task [71].…”
Section: Imaging Of Acetylcholinementioning
confidence: 99%